ARGUMENTS POUR UNE PRODUCTION TÉLÉVISUELLE À L’UNIVERSITÉ: UNE APPROCHE DES LANGUES ÉTRANGÈRES DANS L’ENSEIGNEMENT SUPÉRIEUR ILLUSTRÉE PAR DES FILMS EN ALLEMAND ET EN FRANÇAIS - Giessen Hans (European Scientific Journal, ESJ, 2013)
Television plays an important role in teaching as well as in research of two departments at Saarland University: the Romance language department and the department of information sciences. Thus, the two department have developed a joint "University television project", historically the very first in Germany that broadcasts regularly in the context of a television station that covers an entire federal state within Germany. This paper presents the history, the goals and the types of emissions we broadcast. We have different approaches: one is the production of students that for example try to improve their intercultural and their language skills and deals with how to present information the most succesful way possible. The experiences inside and outside of the university are described.